Towards Institutionalizing Best Practices for Problem Based Learning: Promoting Higher Order Thinking at a Government Co-Educational Sub-Urban Primary School in Tobago - Smith- Rochford, Corine (My University, 2017)
This study sought to implement, institutionalize, and evaluate innovative best-practice approaches for problem-based learning (PBL) to promote higher-order thinking at a coeducational primary school in Tobago. Six teachers were selected to participate in a 12-week professional development programme at the school under study. Data were collected through interviews, observations, and document analysis. The findings revealed a number of factors that could impact the implementation of PBL in the classroom. Analysis of the data showed that professional development workshops facilitated the implementation of PBL and enhanced the teachers’ classroom instruction. However, while they all perceived PBL as positively impacting their students’ critical thinking and problem-solving skills, they identified certain factors that impeded implementation. These were: 1) insufficient time, 2) inadequate resources, and 3) teacher preparedness in relation to planning. Additionally, the teachers all opined that continuous training and professional development were necessary to build their capacity to institutionalize the change process.
Keywords: Action research; Primary school teachers; Teacher attitudes; Coeducational schools; Urban schools; Capacity building; Problem-based learning; Tobago; Trinidad and Tobago